Крестьянские прошения первых веков н. э. из фракийских земель, Малой Азии и Северной Африки: опыт сравнительной характеристики - Мартемьянов, А. П. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryA. Martemyanov. Peasant Petitions of the First Centuries A.D. from the Thracian Lands, Asia Minor and North Africa: the Attempt of the Comparative CharacteristicThe article is devoteed to comparative characteristic of the peasant complaints from Choradagei (Lower Moesia), Scaptopara (Thrace) and analogous petitions from other regions of the Roman Empire. The results of this analysis testify to similarity of the conditions of the country life in the Thracian lands, Asia Minor and  the African possessions of the Rome in the age of the principate. In author’s opinion it prove the possibility of thee attraction of the materials from the Eastern and North-African provinces of the Roman Empire as analogies on the research of the country life of Lower Moesia and Thrace in the first centuries A.D.